Heavy Metal Removal from Wastewater Using Synthesized Silicate-1 Nanocrystal - Muhammad, Syaifullah; Syahputra, Edy; Nasrullah, Nasrullah; Suraiya, Suraiya; Wang, Shaobin; Tade, Moses O. (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2011)
Particle size reduction of zeolite to the nanometer scale leads to substantial changes in the properties of zeolite which make them promising materials for many applications including adsorption. Zeolite silicate-1 Nanocrystal was synthesized at temperatures of 800C, 1200C and 1500C by adding tetrapropylammonium hydroxide (TPAOH) into silica sources. The synthesis mixtures are 2TPAOH: 0.15Na2O: 4.5Si: 382H2O: 51EtOH (TEOS as silica source) and 2TPAOH: 0.15Na2O: 6SiO2: 532H2O: 51EtOH (Ludox LS as silica source). X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) were used to characterize the synthesised products. The nanosilicate-1 particle size were obtained in range of 119 nm 1678 nm. This research also confirmed that TEOS can make smaller particle size up to 36.43 % than Ludox LS due to an average hydrodynamic diameter of 4 nm of TEOS smaller than Ludox LS of 15-19 nm. In the heavy metal adsorption study, it was found that the adsorption capacity indicated by Qmax (Langmuir) and KF (Freundlic) shows higher Pb2+ adsorption than Cr3+. The maximum adsorption capacities of Pb and Cr at 300C are 131.58 mg/g and 129.87 mg/g, respectively. Further, it can also be seen that the KL values in the Langmuir isotherm indicate the higher selectivity of Pb on silicate-1 zeolite than Cr.Keywords :Adsorption capacity, Heavy metal, Isotherm, Silicate-1 nanocrystal